Discourses on the History of Uzbek Principalities of Southern Turkestan in the First Half of the 19th Century - Zayniyevich, Orziyev Mahmud; Baxromovich, Nizamov Asqar (Journal of Innovation in Education and Social Research, 2026)
After the Ashtarkhanid Khanate in Bukhara fell into crisis, the Mangid dynasty came to power. During the period of dynastic change, the Uzbek principalities in South Turkestan, which were subordinate to the Bukhara Khanate, were conquered by the Afghan state founded by Ahmad Shah Durrani, which arose at the same time as the Mangit dynasty. After the death of Ahmad Shah Durrani, the Uzbek principalities were officially considered dependent on Kabul, but in practice they gained independence. In the Bukhara Emirate, Shah Murad tried to establish some internal order and integrate the principalities of South Turkestan into the Bukhara Emirate. During the reign of his successors, Emir Haidar and Emir Nasrullah, some principalities obeyed the Bukhara Emirate. However, with the rise to power of Dost Muhammad Khan, a Barakzai, in Afghanistan, struggles for centralization began. During the First Anglo-Afghan War, the Uzbek principalities in South Turkestan resisted the British’s advance into Central Asia through the Hindu Kush Mountains and even defeated the British troops. After the Anglo-Afghan War, Dostmuhammad Khan, with military support from the British, began to subjugate the Uzbek principalities in South Turkestan in the 50s of the 19th century. He united the conquered territories and named them Chahorvilayat (Four provinces) and appointed his eldest son Muhammad Afzal Khan as the governor.